Genomic characterization of VIM Metallo-β-Lactamase-Producing alcaligenes faecalis from Gaza, Palestine (2017)
ABSTRACT : Carbapenemase-producing Gram-negative bacteria (CP-GNB) have increasingly spread worldwide, and different families of carbapenemases have been identified in various bacterial species. Here, we report the identification of five VIM metallo- -lactamase-producing Alcaligenes faecalis isolates associated with a small outbreak in a large hospital in Gaza, Palestine. Next-generation sequencing analysis showed blaVIM-2 is harbored by a chromosomal genomic island among three strains, while blaVIM-4 is carried by a novel plasmid in two strains.